Compliance with Regulations: Critical Path to Adequate Corporate Governance in the Banking Industry for Business Sustainability and Improved Financial Performance (A Nigeria Case Scenario) - Bejide, Akande Oyebola (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Compliance with regulations remained a significant impediment in the financial industry globally, especially in the Nigerian Banking Industry. Corporate governance is obligatory, but adherence to rules is a puzzle in the banking industry, which has impacted the investors and financial performance considering fines and penalties incurred by the banks where sanctioned. Regardless, compliance issues are global, and regulation needs improved regulatory momentum in the Nigerian financial sector to ensure no ambiguities in the rules of law for its proper understanding and implementation. Consequently, in the current global market, compliance is the only language to fortify the financial industry from any future collapse due to the disposition of the corporate financial leader to their business and codes of corporate governance. The purpose of this qualitative exploratory multiple case study was to explore compliance mitigants corporate financial leaders need to implement to ensure adherence to regulations to improve business sustainability and organizational financial performance. The banking industry is one of the pillars of the economy; however, in Nigeria, average depositors feared the bank due to the constant failure of the banks. This paper contributes to the issue of compliance and its management to avoid an impending collapse in the industry. The sample for this study was 18 corporate financial leaders and regulators with at least ten (10) years of banking and regulatory experience at the top management level involved in strategic positions with a varied portfolio in the banking industry in Nigeria. This paper relies on Agency theory as the conceptual framework for the study because of the inherent issues of conflict of interest in the Banking Sector. Qualitative methodology using semi-structured face-to-face interviews and review of circulars and policies issued by regulators and internal policies of the banks served as the data collection in this study. Data were transcribed, analyzed, and validated using member checking and triangulation. The Participant signed an informed consent form before the commencement of the data collection. The finding revealed that compliance is improving in the Nigerian financial industry. However, there are still issues of noncompliance and problems related to conflict of interest until 2021, which affects the financial performance of the banks in the long run and may lead to financial distress supported by Agency theory as the conceptual framework. The regulators may use the findings to improve on their supervisory, monitoring strategy and guard ambiguity in regulations to ensure that corporate financial leaders are not just complying with the part of the code they are comfortable with but all aspect of the codes of corporate governance and the implementation in alignment with best practices globally. The corporate financial leaders may use the findings to curb the strategies that could impact their business to the point of collapse and imbibe the spirit of the code to ensure the company adhered to regulations for sustainability and going concerned of the company to enhance their financial performance for the improved reputation to attract potential investors. The regulator may use the findings to curb impending collapse in the Banking industry by been proactive instead of being reactive to a crisis in the banking industry.